Improving Student Biology Learning Outcomes through STAD Type Cooperative Learning on Plant Material - JULI ARSISMEN SARI (Bioeducation Journal, 2019)
The learning process carried out at school is expected to be able to increase the learning activities and learning outcomes of students. Student biology learning outcomes and activities at SMAN 1 Koto XI Tarusan are still not satisfactory. The methods and strategies used so far have not been able to improve students' learning activities and outcomes. One of the efforts to increase the activities and learning outcomes of students is through STAD type cooperative learning and the internet as a source of teaching materials. This research was conducted in the even semester of Academic Year 2011/2012 in Class X.7 of SMAN 1 Koto XI Tarusan. This research was conducted in two cycles, each cycle consisting of four stages: planning, implementing, observing, and reflecting. The research data were obtained through observation sheets and learning outcomes tests given at the end of the cycle. The results of the analysis of the data cycle I and cycle II showed an increase in student learning activities and learning outcomes. Student learning activities have increased by 8%, and student learning outcomes have increased by 10%. It can be concluded that the use of STAD cooperative learning types and the internet as a source of teaching materials can increase the activity and learning outcomes of students in class X.7 of SMAN 1 Koto XI Tarusan.